RepA Promotes the Nucleolar Exclusion of the V2 Protein of Mulberry Mosaic Dwarf-Associated Virus - Wang, Dongxue; Sun, Shaoshuang; Ren, Yanxiang; Li, Shifang; Yang, Xiuling; Zhou, Xueping (Frontiers in Microbiology, 2020)
Plant viruses have limited coding capacities so that they rely heavily on the expression of multifunctional viral proteins to achieve a successful infection. The functional specification of viral proteins is often related to their differential interaction with plant and viral components and somewhat depends on their localization to various subcellular compartments. In this study, we analyzed the intracellular localization of the V2 protein of mulberry mosaic dwarf-associated virus (MMDaV), an unsigned species of the family Geminiviridae. We show that the V2 protein colocalizes with the nucleolar protein fibrillarin (NbFib2) in the nucleolus upon transient expression in the epidermal cells of Nicotiana benthamiana. A yeast-two hybrid assay, followed by bimolecular fluorescence complementation assays, demonstrated the specific interaction between V2 and NbFib2. Intriguingly, we find that the presence of MMDaV excludes the V2 protein from the nucleolus to nucleoplasm. We also present evidence that the replication-associated protein A (RepA) protein of MMDaV interacts with V2, enables the nucleolar exclusion of V2, and changes primary nucleolus localization of the site of V2-V2 interaction to the nucleoplasm. We further reveal that RepA promotes V2 out of the nucleolus presumably by directing the NbFib2-V2 complex from the nucleolus to the nucleoplasm. Considering the critical role of the nucleolus in plant virus infection, this RepA-dependent modulation of V2 nucleolar localization would be crucial for understanding the involvement of this subcellular compartment in plant-virus interactions.